2017
DOI: 10.1111/neup.12386
|View full text |Cite
|
Sign up to set email alerts
|

IL‐10 expression in pyramidal neurons after neuropathogenic coronaviral infection

Abstract: The apoptosis of pyramidal neurons in CA2 and CA3 subregions of the hippocampus is induced after infection with Mu-3 virus (Mu-3), a neuropathogenic strain of the JHM virus (JHMV), at 4-5 days post-inoculation (dpi). The viral antigens in the hippocampus are mainly found in the CD11b-positive cells distributed in the stratum oriens located outside the pyramidal layer, and only a few pyramidal neurons are infected. Furthermore, the apoptotic cells, indicated as showing caspase 3 (Cas3) activation, consist of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The results indicated that the protein level of spinal Nrf2 was increased at 2 h post intraperitoneal injection of 200 mg/kg 4-OI ( Figures 9C, D ). Since both the neurons ( 36 , 37 ) and microglia ( 38 ) could produce the IL-10, then we used the N2A cells and BV2 cells to mimic neurons and microglia respectively. We found that after the treatment of 4-OI and 4-OI+LPS, the IL-10 released from the N2A cells was increased compared to that in the vehicle group ( Figure 9E ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the protein level of spinal Nrf2 was increased at 2 h post intraperitoneal injection of 200 mg/kg 4-OI ( Figures 9C, D ). Since both the neurons ( 36 , 37 ) and microglia ( 38 ) could produce the IL-10, then we used the N2A cells and BV2 cells to mimic neurons and microglia respectively. We found that after the treatment of 4-OI and 4-OI+LPS, the IL-10 released from the N2A cells was increased compared to that in the vehicle group ( Figure 9E ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, the IL-10 expression in ipsilateral spinal cord was increased in neurons after systemic injection of 4-OI in CCI mice. Although myeloid cells are the main source of IL-10, there are some studies indicating the IL-10 also can be produced in neurons ( 36 , 37 ), neuronal cell line ( 53 ), and neural stem cells ( 54 ). So, it needs further investigation to explain why 4-OI fails to promote the expression of IL-10 in microglia and elucidate the specific regulation mechanisms of itaconate on neuronal IL-10 production.…”
Section: Discussionmentioning
confidence: 99%